Synthetic lethality between RB-loss and E2F3 inhibition in small cell cancers targeted by pyrimidine synthesis blockade - Evan R. Abt; Liang Wang; Grigor Varuzhanyan; Jack Freeland; Tian He; Guadalupe M. Peña-Garcia; Lauryn Ruegg; Jami McLaughlin; Donghui Cheng; Nikolas G. Balanis; Chia-Chun Chen; Yang Xu; et al. (Proceedings of the National Academy of Sciences, 2026)
Small cell carcinoma is a highly lethal cancer variant often found with neuroendocrine (NE) features, as exemplified by small cell lung cancer and small cell NE prostate cancer (SCPC). A genome-wide CRISPR dependency screen using SCPC models generated through human prostate cell transformation identifies a requirement for the transcription factor E2F3. E2F3 dependency is linked to RB inactivation, a near universal occurrence across small cell cancers. The requirement for E2F3 is shared by RB-deficient cells originating from the prostate, lung, and adnexa. In RB-deficient cancer cells, E2F3 inhibition restrains cell cycle progression, proliferation, and tumor growth in vivo. Inhibition of de novo pyrimidine synthesis limits E2F3 expression and suppresses small cell carcinoma proliferation in culture. Directly or indirectly targeting E2F3 to leverage a pan-cancer synthetic lethality resulting from RB inactivation represents a potential treatment strategy.